The legal expertise subject - Рибікова, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article is devoted to research of the concept and the content of the legal expertise subject. The author in this investigation determines a range of issues of the general legal expertise subject. Law-making process and law implementation require scientifically measuresof control, one of them is the legal expertise. Until now, there is no single theoretical approach to the definition of the legal expertise subject. There is a need to revise and supplement the legal expertisesubject based on the procedure of approximation of Ukraine law to the EU acquis. The legal expertise subject is a flexible system of questions, based on legal criteria of quality.The answerson these questionshelp to detect defects of legal acts andare the base to make recommendations to correct defects of legal acts.Also,the list of questionscannot be developed once and for all, it requires a periodic review. The authordeterminesthe signsof the legal expertise subject: 1. consistency; 2. flexibility; 3. compliance with legal criterion of quality; 4. closecoherencyto the theory of defects of legal acts. The author offers to include the question of checking the adoption of new legal acts to implement the requirements of the object of expertise to the subject of the legal expertise. The legal expertise subject is the central link of the legal expertise, which requires a reasonable and balanced attitude to the formulation of quantitative and qualitative composition of the legal expertise subject.